Different isolates of phomopsis spp. on mikania micranthha H.B.K. - Ida Hani, Ali (Universiti Malaysia Sarawak (UNIMAS), 2005)
Cultures of Phomopsis spp. were obtained from Mikania mierantha disease infected leaves collected from a greenhouse area at Universiti Malaysia Sarawak. Three isolates of Phomopsis were obtained. The effects of different temperature, different media and different light conditions on growth of the fungus isolates were examined. The growth of the fungus at different temperatures were tested at 15°C, 20°C, 25°C, 30°C, 35°C and 40°C. The growth was significantly fastest at P :s 0.05 at temperature range between 20°C-25°C. PDA (potato dextrose agar), MEA (malt extract agar) and CMA (com meal agar) were used as the tested growth media and were incubated at room temperature. The fastest growth for alJ the isolates was on MEA followed by on PDA and on CMA. The effects of light were studied by incubated the fungi under fluorescent light, in dark condition and under Ultraviolet (UY) light at room temperature. The fungal growth showed no significant difference at P ::: 0.05 in the different light conditions. Pathogenicity tests were done using mycelia and pycnidia as the inoculum of this fungus and inoculated on wounded and unwounded healthy leaves of M mierantha in a laboratory and in a greenhouse. No disease symptoms were developed on the wounded and unwounded leaves indicating that the fungal isolates were not pathogenic to the host plant.